Digital image processing concepts, algorithms, and scientific applications - Jahne, Bernd (Springer, 1997)
The fourth edition of this book has been revised and expanded to reflect the development of the field. The presentation and the selection of materials is guided by the needs of a researcher who wants to apply image processing techniques in his or her field. In this sense the book offers an integral view of image processing from image acquisition to the extraction of the data interest. The discussion of the general concepts is supplemented with examples from applications on PC-based image processing systems and ready-to-use implementations of important algorithms. The CD-ROM contains examples and images as well as exercises for self-study along with a hands-on version of the image processing software Heurisko.